Let's solve your equation step-by-step.
(−
1
/5
)(c)+2+c=
1
/5 (10c−20)
Step 1: Simplify both sides of the equation.
(−
1
/5
)(c)+2+c=
1
/5
(10c−20)
(−
1
/5
)(c)+2+c=(
1
/5
)(10c)+(
1
/5
)(−20) (Distribute)
−1
/5
c+2+c=2c+−4
(
−1
/5
c+c)+(2)=2c−4 (Combine Like Terms)
4
/5
c+2=2c−4
4
/5
c+2=2c−4
Step 2: Subtract 2c from both sides.
4/5
c+2−2c=2c−4−2c
−6
/5
c+2=−4
Step 3: Subtract 2 from both sides.
−6
/5
c+2−2=−4−2
−6
/5
c=−6
Step 4: Multiply both sides by 5/(-6).
(
5
/−6
)*(
−6
/5
c)=(
5
/−6
)*(−6)
c=5
Answer:
c=5
Answer:
D. mAngle15 = 97°
explanation:
Just took the test :) good luck!
Answer:
14
Step-by-step explanation: